Assessment of the economic, environmental and safety impact of biofouling on a ship's hull and propeller - Liu, Shukui (2023)
This paper presents a transparent methodology for predicting the speed/power performance of a ship under various conditions, considering the influence of biofouling on ship's hull and propeller. The biofouling development on ship surfaces are represented by surface roughness and their influence on ship performance are accounted for following Granville's model for hull resistance and an ITTC examined model for propeller characteristics, respectively. The established methodology is applied to the examination of the performance of a tanker under adverse conditions and typical service conditions. For the minimum power, we discuss the importance of implementing a suitable numerical method for determining the propeller operation point. Results show that the power reserve will decrease with the roughness increase. In service conditions, the required power increases with the fouling development. Under certain fouled conditions, the service speed cannot be achieved. Lastly, the fuel consumption and associated cost and GHG emission are calculated for a given voyage and the result signifies the tremendous impact of biofouling development on ship operation. The innovation of the work refers to its capability of analysing the influence of the roughness development on hull and propeller surfaces separately using minimum amount of ship information.